Light absorption properties of the rabbit cornea repeatedly irradiated with UVB rays - Cejka, Cestmír; Pláteník, Jan; Guryca, Vilém; Sirc, Jakub; Michálek, Jirí; Brůnová, Blanka; Cejková, Jitka (Photochemistry and photobiology, 2007)
Under normal conditions, the cornea absorbs the majority of UVB (ultraviolet B, 280-320 nm) rays, which is very important for the protection of the inner eye against their damaging effect. Our previous studies have shown that repeated irradiation of the rabbit cornea with UVB rays for 5 days (daily dose of 1.01 J cm(- 2)) caused photokeratitis accompanied by swelling (hydration) of the corneal stroma, thinning of the corneal epithelium and decrease in antioxidants. The purpose of this study was to examine the light absorption properties of such damaged rabbit cornea. Results of both spectrophotometry of the whole corneal buttons and corneal tissue dissolved in sodium hydroxide show that because of above mentioned disturbances, UVB-irradiated cornea absorbs more light throughout the whole measurable UV-VIS spectral range than the normal cornea. Increased corneal thickness (result of hydration), changes of corneal transparency (the cornea becomes grayish) and some increase in protein content all contribute to the increased light absorption of UVB irradiated corneas. We suggest that the UVB-irradiated cornea, although damaged and nearly without antioxidants, might actually through its higher UV absorbance protect the inner eye against further damage from UVB rays.
Keywords: ultrafialové záření; králíci; Epithelium, Corneal; rohovka; antioxidancia; keratitida; Cornea; Ultraviolet Rays; Animals; rohovkový epitel; Antioxidants; zvířata; Rabbits; Stromal Cells; buňky stromatu; Keratitis